Estudo da cafeína anidra sob condições extremas através de espectroscoia Raman - Maia, José Robson (2010)
In this work anidrous cafeine (C8H10N4O2) crystals were investigated through the Raman spectroscopy technique, with change of temperature and pressure, in the spectral region between 30 and 3200 cm-1 In the temperature experiments the thermodynamic parameter changed from 23 and 170 0C. From them it was possible to realize that anidrous cafeine undergoes a structural phase transition at about 140 0C, as pointed by the disappearance of three bands associated to external modes. After sample goes back to room temperature, it is observed that the original Raman spectrum was not recovered, indicating that the transition is not reversible. Thermal analysis experiment confirms the structural phase transition undergone by cafeine. In order to perform high pressure experiments we have used a diamond anvil cell, being possible to arrive to pressures up to 10.6 GPa. In the high pressure Raman experiments it was possible to observe a phase transition at about 1 GPa, as indicated by the appearance of a band at 37 cm-1 as well as a second phase transition between 6.2 and 7.5 GPa. This last phase transition was characterized by the discontinuity in the frequency band of two low energy. In the pressure range 7.3-10.6 GPa, the Raman scattering experiments performed on anidrous cafeine showed indicious of lost of long range order, which was interpreted as a possible amorphization of the sample.